(untitled) (Al-Mukhtar Journal of Legal Science, 2025)
The research addressed the issue of implementing the annulment ruling, using a comparative approach that combined the Libyan and Egyptian systems. It concluded that the administrative judiciary is well-established in that the jurisdiction of the administrative judge in an annulment suit is limited to annulling the unlawful decision, and does not extend to replacing the administration, issuing orders to it, or obligating it to implement the ruling in a specific manner. The administration’s obligation to implement annulment rulings is subject to judicial oversight exercised by the courts. The Libyan system has been greatly influenced by the Egyptian system, in confronting the administration’s refusal to implement annulment rulings. The research’s most important recommendations are embodied in the call for the Libyan legislator to stipulate that the administrative judiciary must communicate with the administration regarding the implementation of administrative annulment ruling.